Managing medications for individuals living with a dementia: Evaluating a web‐based information resource for informal carers. (10th May 2018) - Horne, Frances; Burns, Pippa; Traynor, Victoria; Gillespie, Robyn; Mullan, Judy; Baker, Amanda; Harrison, Lindsey; Win, Khin Than
Abstract : Aims: The purpose of the study was to evaluate the usefulness of the "Managing Medicines for People with Dementia" (www.dementiameds.com ) website for informal carers. Background: The management of medications for individuals living with a dementia by informal carers is a neglected area of care. We know that informal carers find it difficult accessing reliable and comprehensive information about medications. We also know that the Internet is a contemporary and growing medium through which consumers access health information. This study was unique in that it brought these two elements together through an interdisciplinary study about the usefulness of a new website providing information on medication management. Methods: Data collection consisted of focus groups with informal carers of individuals living with a dementia. Data were analysed through content analysis. Findings: Four themes were generated from the data to explain the evaluation of the website by informal carers: (1) Suitability of the website; (2) Presentation of the website; (3) Unexpected benefits of the website content; (4) Future enhancements for website. Participants overwhelmingly agreed the content of the website filled a gap in information needs about medication management for individuals living with a dementia. Implications for practice: This qualitative evaluation demonstrated the value of the website as a resource for informal carers of individuals living with a dementia. The resource could also be used by community nurses and other healthcare practitioners to help informal carers better manage the medication regimes of individuals living with a dementia. The resource has the potential to reduce complications associated with mismanagement of medications and contribute to new policies for implementing safe medication practices.